ANALISIS KERENTANAN BENCANA GERAKAN TANAH DI KECAMATAN KAPALA PITU KABUPATEN TORAJA UTARA - Eki Paska Kombong (Jurnal Manajemen Bencana (JMB), 2023)
Land movement disasters occur frequently, and their number is increasing in Indonesia. North Toraja Regency is an area prone to land movement or landslides with medium to high levels. This study aims to determine the level of knowledge, attitude, community action (practice) towards land movement disasters, find out the vulnerability of land movement disasters and compile land movement disaster mitigation plans in Kapala Pitu District, North Toraja Regency. This study is deductive with a mixed methods approach conducted from March to May 2023 with 90 samples. This study obtained data for descriptive analysis through questionnaire instruments, while in order to measure the level of hazard quantitatively, sampling and laboratory tests and modeling with Slope/W were carried out through the Geo Studio application. The results showed that 54.4% of people have low knowledge, 50% of people have a positive attitude and good actions in applying rules and knowledge in reducing land movement disasters by 50%. These results suggest that some communities have a high vulnerability to land movement disasters. In reviewing the hazard level of ground movement, stability analysis generally produced a safety factor (SF) of <1 above 30° slope, while 82% of the study area had a slope above 40°, so it was assessed to have a high level of ground movement hazard.